Disruptively regional: How women in Regional, Rural and Remote communities ‘imagine’ with and through digital and social media - Tara BRABAZON; Jacqueline EWART (Smart Cities and Regional Development Journal)
Too often, regional, rural and remote cities and towns are configured in deficit to the metropolis.  As local newspapers have closed, how are local stories gathered, understood, published and disseminated?  The objective of this article probes how women leaders in the media industries deploy their lived experiences to re/shape, reimagine and sustain regional, rural and remote life through digitizing community leadership. We explore how technology provides new opportunities to share stories of women’s strength and capacity to build new pathways between information and citizens.  Using original interviews, we investigate how women in these locations use the internet and digitization to share stories of their communities and culture to metropolitan environments in the absence of truly local news outlets, bypassing traditional news media and taking control of how their stories are told. This approach to the research demonstrates that alternative modes of ‘writing back’ are emerging.  Certainly, analogue injustices overlay digital inequalities. However, the opportunities and potential for resistance and interventions are revealed and disseminated the courage, direction and gumption of women summoning a different mode of media leadership that is critiques and transforms traditional models of ownership, production, and consumption.  The implications of this paper are important, as we offer a fresh model to think about regional media and regional media leadership.  Yet the value of this research transcends media, summoning a model of social, cultural, and economic transformation, through digitization, disintermediation and deterritorialization.